Design of multiband multipolarised single feed patch antenna. Issue 15 (19th October 2018) - Dabas, Tanvi; Kanaujia, Binod Kumar; Gangwar, Deepak; Gautam, Anil Kumar; Rambabu, Karumudi
Abstract : A new low profile, multiband, multipolarised single feed antenna is designed. A corner truncated patch loaded with slots and a complementary split ring resonator is used to achieve three frequency bands with different polarisations. The antenna exhibits right‐hand circular, linear, and left‐hand circular polarisation at three different bands, respectively. To obtain circular polarisation, orthogonal modes are excited by truncating corners of the patch and etching slits. Single feed, single layer geometry with Y‐shaped feed structure is employed. The antenna is fabricated on a low‐cost FR4 substrate with an overall size of 70 mm × 70 mm, and the proposed design has been verified experimentally. The selected frequency bands are centred at 2.313, 2.396, and 2.478 GHz, and they have −10 dB impedance bandwidths of 2.14, 2.50, and 2.42%, respectively. The first frequency band exhibits right‐hand circular polarisation with a 3 dB axial ratio bandwidth of 0.85%. The second frequency band exhibits linear polarisation, whereas the third frequency band exhibits left‐hand circular polarisation with a 3 dB axial ratio bandwidth of 0.81%.